Effects of an acute exercise bout in hypoxia on extracellular vesicle release in healthy and prediabetic subjects - Warnier, Geoffrey; De Groote, Estelle; Britto, Florian A.; Delcorte, Ophélie; Nederveen, Joshua P.; Nilsson, Mats I.; Pierreux, Christophe E.; Tarnopolsky, Mark A.; Deldicque, Louise (American journal of physiology. Regulatory, integrative and comparative physiology, 2022)
The purpose of this study is to investigate exosome-like vesicle (ELV) plasma concentrations and markers of multivesicular body (MVB) biogenesis in skeletal muscle in response to acute exercise. Seventeen healthy [body mass index (BMI): 23.5 ± 0.5 kg·m −2 ] and 15 prediabetic (BMI: 27.3 ± 1.2 kg·m −2 ) men were randomly assigned to two groups performing an acute cycling bout in normoxia or hypoxia ([Formula: see text] 14.0%). Venous blood samples were taken before (T0), during (T30), and after (T60) exercise, and biopsies from m. vastus lateralis were collected before and after exercise. Plasma ELVs were isolated by size exclusion chromatography, counted by nanoparticle tracking analysis (NTA), and characterized according to international standards, followed by expression analyses of canonical ELV markers in skeletal muscle. In the healthy normoxic group, the total number of particles in the plasma increased during exercise from T0 to T30 (+313%) followed by a decrease from T30 to T60 (−53%). In the same group, an increase in TSG101, CD81, and HSP60 protein expression was measured after exercise in plasma ELVs; however, in the prediabetic group, the total number of particles in the plasma was not affected by exercise. The mRNA content of TSG101, ALIX, and CD9 was upregulated in skeletal muscle after exercise in normoxia, whereas CD9 and CD81 were downregulated in hypoxia. ELV plasma abundance increased in response to acute aerobic exercise in healthy subjects in normoxia, but not in prediabetic subjects, nor in hypoxia. Skeletal muscle analyses suggested that this tissue did not likely play a major role of the exercise-induced increase in circulating ELVs.